Inducing molecular orientation in solution-processed thin films of fluorene-bithiophene-based copolymer: thermal annealing vs. solvent additive - Coutinho Pereira, Cassia Ferreira; Borges, Bruno G. A. L.; Sousa, Karlison R. A.; Holakoei, Soheila; Roman, Lucimara S.; Araujo, C. Moyses; Cremona, Marco; Koehler, Marlus; Marchiori, Cleber F. N.; Rocco, Maria Luiza M. (RSC advances, 2024)
A deep understanding of the factors influencing the morphology of thin films based on conjugated polymers is essential to boost their performance in optoelectronic devices. Herein, we investigated the electronic structure and morphology of thin films of the copolymer poly(9,9-dioctyl-fluorenyl- co -bithiophene) (F8T2) in its pristine form as well as samples processed with the solvent additive 1,8-diiodooctane (DIO) or post-processed through thermal annealing treatment. Measurements were carried out using angle-resolved S K-edge NEXAFS (near-edge X-ray absorption fine structure) in total electron yield (TEY) and fluorescence yield (FY) detection modes. Two main transitions were observed at the S 1s NEXAFS spectra: S 1s → π* and S 1s → σ* (S–C). The observed dichroism pointed to a face-on orientation of the conjugated backbone, which was significantly increased for F8T2 films processed with DIO. Resonant Auger decay spectra were obtained and analyzed using the core-hole clock (CHC) method. An enhancement in the charge transfer process was observed for thermally annealed films, especially for samples processed with DIO, corresponding to an increase in film ordering. Furthermore, the investigated films were characterized using X-ray photoelectron spectroscopy, attesting to the presence of the thiophene unit in the samples and demonstrating that some of its sulfur atoms were positively polarized in the F8T2 films. All these experimental findings were compared with molecular dynamics (MD) simulations of film evaporation with and without DIO. The use of MD, together with mathematical modeling, was able to explain the major effects found in the experiments, including the polarization of sulfur atoms. The simultaneous use of powerful spectroscopic techniques and theoretical methods shed light on key aspects linking film morphology with fabrication procedures.